Efektivitas Hukum Pidana dalam Melindungi Perempuan Korban Kekerasan Seksual di Era Sekarang dan Mendatang - Yazid Bustomi (Faculty of Law, Andalas University, 2020)
The aim of this study is to analyse how the effectiveness of criminal law regulations in protecting women victim of sexual violence. The method used in this research is the statue approach and conceptual approach. This research was conducted by collecting primary and secondary legal materials, in order to obtain a critical study of the legal issues that surround the community. The results of this study state that the existing criminal law regulations, Penal Code of Indonesia and Code of Criminal Procedure (KUHP and KUHAP) and future criminal law regulations (RKUHP and RUU PKS) are less effective. This research found about the ambiguity of the definition and meaning of the acts that are regulated is not very broad, so that it has the potential to cause a gap for the perpetrators to commit crimes and the perpetrators will escape the bondage of criminal law. So, the renewal of regulations needs to be done to guarantee and protect women's rights by taking into account all possibilities of types of crimes and new modes that will be committed in the future.